Robustness of intermediate agreements for the discrete Raiffa solution - Walter Trockel (Bielefeld University, Center for Mathematical Economics (IMW), 2013)
First via a counter example it is shown that the Proposition 3 of Anbarci & Sun (2013) is false. Then a gap and a mistake in their proof are identified. Finally, a modified version of their Proposition 3 is stated and proved.
Keywords: 330